Intellectual Capital, Profitability, and Good Corporate Governance Effects on Company Value - Anugerah Ercy Ekaputra; Lukluk Fuadah; Sa'adah Yuliana (Bina Nusantara University, 2020)
The research aimed to analyze the influence of Intellectual Capital (IC), profitability, and Good Corporate Governance (GCG) on company value indexed in LQ45 in 2014-2015. IC was measured using Value Added Intellectual Coefficient (VAICTM). Meanwhile, Return on Asset (ROA) and Return on Equity (ROE) measured profitability, and institutional ownership and managerial ownership were measured for GCG. The sample was all companies registered in LQ45 from 2014 to 2018. The researchers used multiple regression analysis method. Based on the test results of the coefficient of determination (R2), it obtains a value of 0,785. It means IC, profitability, and GCG can explain the company value at 78,5%, while other 21,5% are from other variables. The results show that IC, ROA, institutional ownership, and managerial ownership have no significant effect on company value. The results also show that only ROE has a significant impact on company value.